2020
DOI: 10.1021/acs.jpcc.9b09973
|View full text |Cite
|
Sign up to set email alerts
|

Optical Index Prism Sensitivity of Surface Plasmon Resonance Imaging in Gas Phase: Experiment versus Theory

Abstract: Recent advances in SPR-imaging detection in gas phase have led to the development of opto-electronic noses (opto-eNs) requiring the need for optical sensitivity characterization of such devices. Understanding of the optical contributions will have an implicit relevance on sensitivity enhancement of SPR-imaging in gas phase valuable to improve the performance of opto-eN and potentially open new applications as gas sensors. In this paper, we analyzed the optical contributions to the sensitivity of the SPR imagin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 44 publications
(95 reference statements)
0
19
0
Order By: Relevance
“…A recent study by Weerakkody et al. used Maxwell Garnet mixing theory to generate an anisotropic effective permittivity that accounts for the effects of surface topology within a transfer matrix model . However, the mixing formula was derived assuming ellipsoidal inclusions .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study by Weerakkody et al. used Maxwell Garnet mixing theory to generate an anisotropic effective permittivity that accounts for the effects of surface topology within a transfer matrix model . However, the mixing formula was derived assuming ellipsoidal inclusions .…”
Section: Resultsmentioning
confidence: 99%
“…A recent study by Weerakkody et al used Maxwell Garnet mixing theory to generate an anisotropic effective permittivity that accounts for the effects of surface topology within a transfer matrix model. 40 However, the mixing formula was derived assuming ellipsoidal inclusions. 41 For sparsely distributed microgels with a hemispherical profile and gold islands that follow the topology of the microgel surface, this ellipsoidal approximation is not accurate.…”
Section: ■ Introductionmentioning
confidence: 99%
“…These systems were limited in terms of sensitivity and selectivity based on only one or few sensitive chemical layers. Since 2000, an increasing number of articles can be found in the literature using both biological and organic sensitive materials [185][186][187][188][189][190][191][192][193][194][195][196][197][198][199][200][201][202][203][204]. It has been demonstrated that SPR is very effective for sensing VOCs in the gas phase.…”
Section: Detection Of Vocs In Gas Phasementioning
confidence: 99%
“…Furthermore, we investigated the optical contributions to the sensitivity of the SPR imaging [187]. For this, an original characterization method, which was independent of the carrier gas, was established for the SPR prism sensitivity based on pressure jumps [205].…”
Section: Detection Of Vocs In Gas Phasementioning
confidence: 99%
“…One of the attractive features of peptides is the possibility to obtain a particular binding ability designing a sequence by molecular modeling. Using this concept and starting from a sequence in the P 30953 receptor protein (Swiss prot G databank) in 2011, Sankaran et al [ 67 ] obtained the synthetic peptide Ps17 designed for alcohols. Ps17 was immobilized onto 10 MHz QCMs by SAM and tested with hexanol and pentanol.…”
Section: Peptides Dna and Mips As Sensing Elementsmentioning
confidence: 99%